ANALISIS FAKTOR RESIKO PENULARAN HIV/AIDS DI KOTA MEDAN - Erledis Simanjuntak (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
HIV/AIDS is also a Global Health problem. In all Cauntries are being at risk by the spread of this deadly virus. Not only indevelopment Countries, but also in developing countries such as Indonesia, include in Medan City. Many risk factors of HIV/AIDS are : free sex (at risk), Injecting drug Use, Transmission by blood transfusion, and transmission from mother to child. Moreover the characteristic factors also contribute to the risk of transmission of HIV/AIDS, such as age, gender, occupation, and education. The Study design is Case Control, and 230 subjects (115 Case :115 Control). The Data retrieved from HIV/AIDS patients and Control of Adam Malik Hospital Medan in 2010, the sample is domiciled in Medan City. Descriptive analysis, bivariate analysis (Chi-Square Test), and Multivariate (Logistic Regression test), with SPSS Program for Windos 17. Results show significant relationship with 95 % convidence interval for variable: Injecting Drug Use (P=0,000), free sex (at risk) (P=0,000), Age 15 – 24 years, Age 25-34 years, age 35- 44 years (P=0,000), Male sex (P=0,000), No Work, entrepreneur, privat employees (P= 0,000), primary school, junior high school (P=0,000), senior high school (P=0,001). The result of logistic regression test shows dominant risk factors wich transmission HIV/AIDS in Medan City are : Injecting Drug Use (OR=66,551), free sex (at risk) (OR=25,419), Low education (OR=2,653), No Work (OR= 2,288).